Produção de abacaxi com hortelã em pó por spray drying - Braga, Vanessa (2019)
The objective of this work was to evaluate the effect of the conditions of the drying process of pineapple juice with peppermint spray drying on the physicochemical characteristics of the powders obtained. For this, a central orthogonal composite planning (COCP) was performed, in which the variables studied and the bands corresponding to the -1 and +1 was: the temperature of the drying air (90°C to 120°C), the feed rate of the solution in the dryer (0,4 to 0,8 L.h-1) and the drying air flow rate (1,60 a 1,90 m3.min-1) and the responses were: process yield (%), moisture, water activity (aw), hygroscopicity (%), solubility (%) and color (L *, a * and b *). In addition, the direction of the addition of 0, 3, 7 and 15% of maltodextrin in the juice before the drying process in the studied responses was, analyzed scanning electron microscopy and wetting time. A second planning was done evaluating the same responses and variables, adding 3% of maltodextrin as carrier agent and considering it a process variable. Drying without carrier at the conditions of the central points: drying air temperature (105°C), flow rate of the solution in the dryer (0,6 L.h-1) and the drying air flow rate (1,75 m3.min-1) resulted in up to 35% yield, 0,1850,003 (g water. g -1 dry sol), 0,2100,003 water activity, 99.6% solubility, and obtaining powders with visually green coloration, desirable in a powder of pineapple juice with mint.The presence of maltodextrin contributed to increase the luminosity of the powders and to decrease the intensity of the parameters a * and b * in relation to the powders without the carrier agent dried under the same conditions. The carrier agent also decreased the hygroscopicity, moisture, aw of the powders and increased the drying yield resulting in values up to 54% even when added in low amount (3% over the total sample mass). The powders with 3% maltodextrin also presented higher moisture value in the monolayer (Xm) and decreased the adsorption capacity of powders stored in relative moisture higher than 50% when compared to powders without carrier agent. Thus, drying of pineapple juice with peppermint spray drying as much as possible as maltodextrin was possible, but also the use of the carrier agent even in small quantities for the main components in the drying process such as increased yield and also in the stability of the pos, because it reduced the hygroscopicity of the same in relation to the products without the presence of the agent.